A systematic review and meta-analysis of mortality in chronic Chagas cardiomyopathy versus other cardiomyopathies: higher risk or fiction? = Revisión sistemática y metanálisis de la mortalidad en la miocardiopatía chagásica crónica frente a otras miocardiopatías : ¿mayor riesgo o ficción? - Gómez Ochoa, Sergio Alejandro; Serrano-García, Angie Yarlady; Hurtado-Ortiz, Alexandra; Aceros, Andrea; Rojas, Lyda Z.; Echeverría, Luis E. (Revista española de cardiología. English version, 2024)
Introduction and objectives - Although multiple studies suggest that chronic Chagas cardiomyopathy (CCC) has higher mortality than other cardiomyopathies, the absence of meta-analyses supporting this perspective limits the possibility of generating robust conclusions. The aim of this study was to systematically evaluate the current evidence on mortality risk in CCC compared with that of other cardiomyopathies. - Methods - PubMed/Medline and EMBASE were searched for studies comparing mortality risk between patients with CCC and those with other cardiomyopathies, including in the latter nonischemic cardiomyopathy (NICM), ischemic cardiomyopathy, and non-Chagas cardiomyopathy (nonCC). A random-effects meta-analysis was performed to combine the effects of the evaluated studies. - Results - A total of 37 studies evaluating 17 949 patients were included. Patients with CCC had a significantly higher mortality risk compared with patients with NICM (HR, 2.04; 95%CI, 1.60-2.60; I2, 47%; 8 studies) and non-CC (HR, 2.26; 95%CI, 1.65-3.10; I2, 71%; 11 studies), while no significant association was observed compared with patients with ischemic cardiomyopathy (HR, 1.72; 95%CI, 0.80-3.66; I2, 69%; 4 studies) in the adjusted-measures meta-analysis. - Conclusions - Patients with CCC have an almost 2-fold increased mortality risk compared with individuals with heart failure secondary to other etiologies. This finding highlights the need for effective public policies and targeted research initiatives to optimally address the challenges of CCC. - Resumen - Introducción y objetivos - Aunque múltiples estudios indican una mayor mortalidad en la miocardiopatía de Chagas crónica (MCC) en comparación con otras miocardiopatías, la ausencia de metanálisis que respalden esta perspectiva limita la posibilidad de generar conclusiones robustas respecto a este fenómeno. El objetivo de este estudio es evaluar de manera sistemática la evidencia actual respecto al riesgo de mortalidad en la MCC respecto a otras miocardiopatías. - Métodos - Se realizaron búsquedas en PubMed/Medline y EMBASE de estudios que compararan el riesgo de mortalidad entre pacientes con MCC y con otras miocardiopatías, como la miocardiopatía no isquémica (MNI), la miocardiopatía isquémica y la miocardiopatía no chagásica (MNC). Se realizó un metanálisis de efectos aleatorios para combinar los efectos de los estudios evaluados. - Resultados - Se incluyeron 37 estudios que evaluaron a 17.949 pacientes. Los pacientes con MCC presentaron un riesgo de mortalidad significativamente mayor en comparación con los pacientes con MNI (HR=2,04; IC95%, 1,60-2,60; I2, 47%; 8 estudios) y MNC (HR=2,26; IC95%, 1,65-3,10; I2, 71%; 11 estudios). Sin embargo, no se observó ningún efecto significativo entre los grupos con MCC y con miocardiopatía isquémica (HR=1,72; IC95%, 0,80-3,66; I2, 69%; 4 estudios) en el metanálisis de efectos ajustados. - Conclusiones - Los pacientes con MCC se enfrentan a un riesgo de mortalidad casi 2 veces mayor en comparación con los individuos con otras etiologías de miocardiopatía isquémica. Este resultado pone de relieve la necesidad de políticas públicas eficaces e iniciativas de investigación centradas en abordar de manera óptima los retos de la MCC.
Gesehen am 10.04.2025